Impact of personal protective equipment leachates on early plant development - Mészáros Enikő; Kovács Kamilla; Kovács Etelka; Hoffmann Klaudia; Perei Katalin; Bodor Attila; Feigl Gábor; 30th International Symposium on Analytical and Environmental Problems Szeged 2024. október 7-8. (University of Szeged Szeged, 2024)
The increased disposal of personal protective equipment, such as face masks and gloves, during the global pandemic caused by the novel coronavirus (Covid-19) has led to a notable rise in plastic pollution, which represents a significant ecological threat. This study examines the impact of leachates from polypropylene masks and both latex and nitrile gloves on the early development of twelve plant species, utilising an in vitro semi-hydroponic system. The germination and root growth of the plants were assessed, and Fourier transform infrared spectroscopy was employed to analyse the ageing of the materials. The findings revealed a range of effects of leachates on plant development. The root growth of species such as crimson clover, radish, and buckwheat was found to be inhibited, while other species, including rapeseed, white mustard, and cress, exhibited enhanced growth. The germination index, which integrates relative germination and root length, was utilised to evaluate plant responses. The Brassicaceae species exhibited distinctive responses, with radish displaying high sensitivity to glove leachates, while rapeseed, white mustard, and cress frequently demonstrated growth stimulation. At the family level, legumes exhibited the greatest sensitivity, while monocotyledons were minimally affected, and growth of the Brassicaceae family was generally enhanced. The least reduction in the germination index was observed in the case of mask leachates, in comparison to latex and nitrile gloves. Furthermore, a correlation was identified between root growth responses and material ageing, indicating that masks exhibiting minimal signs of ageing had a comparatively reduced impact on early root development in comparison to aged gloves. The findings of this study emphasise the intricate relationships between plastic leachates from personal protective equipment and plant growth, underscoring the necessity for further investigation in this field.
Keywords: Természettudományok; Föld- és kapcsolódó környezettudományok; Biológiai tudományok